Muslim women and sports in the Malay world the crossroads of modernity and faith - Wirdati Mohammad Radzi (Islam in Southeast Asia: views from within, 2006)
Examines the challenges faced by young Muslim female athletes from Malaysia, Brunei, and Indonesia in competitive sports. This book focuses on social dynamics, and the emergence of Muslim women competing on international level. It captures the athletes' experiences and perspectives as they compete under rules that conflict with Islamic practice